Shopping Motivation, Optimum Stimulation Level, Cognitive Response and Store Patronage Satisfaction: A Case of Indonesia - Budisantoso, Tjong; Mizerski, Kate (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2006)
This study focuses on the relationship between shopping motivation including t he optimum stimulation level and cognitive response and store patronage satisfaction. Shopping motivation focuses o n hedonic shopping motivations while cognitive response is measured in terms of the perception o f merchandise quality and the perception of service quality. T he findings show a moderate relationship between shopping motivation and the perception of merchandise quality and the perception of service quality.A highly significant correlation exists between the perception of merchandise quality and t he perception of service quality and store patronages satisfaction